UV and γ-ray resistance of poly(N-methylmaleimide-alt-isobutene) and poly(diisopropyl fumarate) as transparent polymer films. (September 2017) - Imaizumi, Ryota; Furuta, Masakazu; Okamura, Haruyuki; Matsumoto, Akikazu
Abstract: UV and γ-ray resistance of transparent polymers obtained by radical polymerization of maleic and fumaric acid derivatives, i.e., an alternating copolymer of N -methylmaleimide and isobutene (PMI) and poly(diisopropyl fumarate) (PDiPF), was investigated. Transmittance in UV and visible regions of these polymers were examined after UV irradiation and compared with the results for poly(methyl methacrylate) (PMMA) and polycarbonate (PC) as conventional transparent polymers. The order of stability toward UV irradiation was PMMA≈PDiPF>PMI>>PC, deduced from changes in the transmittance of 380 nm light. Tensile mechanical properties, such as elastic modulus, maximum strength, and elongation values of PMI, PDiPF, and PMMA were also investigated after UV and γ-radiation. UV irradiation induced the side chain scission of PMI and PDiPF via Norrish I type reaction as well as crosslinking by combination between formed polymer radicals, leading to deterioration in their optical and mechanical properties. γ-radiation induced significant changes in molecular weight and mechanical properties of the polymers. In conclusion, PMI exhibited unchanged mechanical properties and PDiPF maintained its high transparency under various irradiation conditions. Highlights: UV- and γ-resistance of PMI and PDiPF as transparent polymers was investigated. UV- and γ-radiations induced the chain scission and crosslinking of these polymers. γ-radiation resulted in significant changes in structure and properties of the polymers. Degradation mechanism of PMI and DiPF was discussed.